Better Executive Functions Are Associated With More Efficient Cognitive Pain Modulation in Older Adults: An fMRI Study - Rischer, Katharina M.; Anton, Fernand; González-Roldán, Ana M.; Montoya, Pedro; van der Meulen, Marian (Frontiers in Aging Neuroscience, 2022)
Growing evidence suggests that aging is associated with less efficient endogenous pain modulation as demonstrated by reduced conditioned pain modulation, and that these changes may be mediated by differences in frontal functioning. Yet, little is known about potential age-related changes in cognitive pain modulation, such as distraction from pain. In a first session, 30 healthy young (19–35 years) and 30 healthy older (59–82 years) adults completed a battery of neuropsychological tests. In a second session, we acquired functional brain images while participants completed a working memory task with two levels of cognitive load (high vs. low) and concurrently received individually adjusted heat stimuli (warm vs. painful). In both age groups, completing the high load task was associated with a significant reduction in the perceived intensity and unpleasantness of painful stimuli and a reduction in activation of brain regions involved in pain processing. Group comparisons revealed that young adults showed a stronger de-activation of brain regions involved in pain processing during the high load vs. the low load task, such as the right insula, right mid cingulate cortex and left supramarginal gyrus, compared to older adults. Older adults, on the other hand, showed an increased activation in the anterior cingulate cortex during the high load vs. low load task, when compared to young adults. Covariate analyses indicated that executive functions significantly predicted neural pain modulation in older adults: Better executive functions were associated with a more pronounced de-activation of the insula, thalamus and primary somatosensory cortex and increased activation of prefrontal regions during the high vs. low load task. These findings suggest that cognitive pain modulation is altered in older age and that the preservation of executive functions may have beneficial effects on the efficacy of distraction from pain.